Sistem Informasi Geografis Tempat Pembuangan Sampah Berbasis Android Di Kota Gorontalo - Alang, Alang; Husain, Hariati (JURNAL TEKNIK INFORMATIKA, 2020)
The population of Gorontalo city is likely to increase because it is the provincial capital which is the center of economy and business. The increasing number of people is increasing the potential for landfill. some people who are less aware of cleanliness will dispose of garbage indiscriminately if they do not know the nearest landfill from their home. Garbage buildup will pollute the environment so that it can interfere with public health and can also cause problems in the future such as flood disasters. Today's problems are often solved by the use of technology, especially information and communication technology. Waste processing can most likely be overcome by using information and communication technology through high mobility media such as smartphones. Today's thriving smartphones are smartphones with android operating systems. Android smartphones besides having high mobility, also have very useful features such as google maps and GPS. Google maps and GPS features can collaborate in an android app program creation. Application program creation is designed using android and PHP programming languages collaborated with MySQL databases as data container media. The application program will be made reliable to solve the problem of waste processing by utilizing Google maps as a means to see landfills (TPS) and GPS as a means to detect the position of people or places that have garbage. Designed applications are expected to provide information on the nearest landfill (TPS) in the area where people live so that there is no garbage buildup, problems in the future such as health problems and flooding